A New Paradigm in Diabetic Nephropathy: Early Progressive Renal Decline - Hoyle, Brian (MD Conference Express, 2014)
The microalbuminuria model of nephropathy in patients with type 1 diabetes mellitus (T1DM) may no longer be valid and may be replaced by the model of early progressive renal decline (EPRD), according to new data that support the latter. This article discusses EPRD as the new paradigm in nephropathy in patients with T1DM.